From “participation” to “transformative participation”: My living-educationaltheory of Facilitating Transformative Continuing Professional Development - Samantha Kahts-Kramer (Educational Journal of Living Theories)
Driven by a strong desire for change and personal values, I began to embrace a participation-orientated approach to my own Continuing Professional Development (CPD), rather than the expert-driven one I had previously employed. In an effort to address past instances in which my actions did not align with my values, I developed my living-educational-theory. I collaborated with various stakeholders, including ten primary school teachers working in low-resource South African schools. I actively refined my evolving educational beliefs by seeking feedback from several of my expert critical friends. Through rigorous reflection, I formulated my research question: "How do I interpret participation as a CPD facilitator in fields such as Physical Education (PE), and how can this understanding be effectively conveyed to others?” Drawing upon insights gleaned from my doctoral research, embedded in Participatory Action Learning and Action Research (PALAR), and my annotated reflections, I identified transformative participation as a core value driving my practice. Consequently, by putting this value into action, I discovered the importance of how to dismantle established norms, recognising and respecting the boundary between personal-professional development, and cultivating leadership for lasting impact. This knowledge informs my decision to share practical insights and standards of judgment to assess how I have adopted transformative participation. My hope is that these insights may assist colleagues seeking to facilitate transformative CPD.